Preoperative electrophysiological characterization of patients with primary macula-involving rhegmatogenous retinal detachment - Jonathan B Lin; Julia Sein; Gregory P Van Stavern; Rajendra S Apte (Journal of Ophthalmic & Vision Research, 2018)
Purpose: To determine 1) which components of retinal function are impaired after rhegmatogenous retinal detachment, 2) which outer retinal pathways (rod- or cone-driven) are more severely affected, and 3) whether there is concomitant inner retinal dysfunction. Methods: We conducted a prospective observational study in a large academic institution. We performed preoperative electroretinography on eight patients to assess outer and inner retinal function. In all cases, a comparison between the eye with the detached retina and the control fellow eye was made. Results: Eyes with a detached retina had significantly lower a-wave and b-wave amplitudes with respect to both rod- and cone-dominated testing parameters (P < 0.05) and reduced 30 Hz flicker responses compared to fellow eyes (P < 0.05); the effect size was similar for all significantly reduced parameters (r~0.6). There were no significant differences between eyes with detached retinas and control fellow eyes with respect to b/a-wave ratios, a-wave latencies, or b-wave latencies. Conclusion: Patients with rhegmatogenous retinal detachment have preoperative outer retinal dysfunction equally affecting both rod- and cone-driven pathways, and they have minimal inner retinal dysfunction.